Software Language Engineering Third International Conference, SLE 2010, Eindhoven, The Netherlands, October 12-13, 2010, Revised Selected Papers - Staab, Steffen; van de Brand, Mark (Springer eBooks., 2011)
This book constitutes the thoroughly refereed post-proceedings of the Third International Conference on Software Language Engineering, SLE 2010, held in Eindhoven, The Netherlands, in October 2010. The 24 papers presented were carefully reviewed and selected from 79 submissions. The book also contains the abstracts of two invited talks. The papers are grouped in topical sections on grammarware, metamodeling, evolution, programming, and domain-specific languages. The short papers and demos included deal with modeling and transformations and translations.